2011
DOI: 10.1007/s00348-011-1246-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of a scaled-up passive micromixer with uneven interdigital inlet and teardrop obstruction elements

Abstract: Micromixers are vital components in micro total analysis systems. It is desirable to develop micromixers which are capable of rapidly mixing two or more fluids in a small footprint area, while minimizing mechanical losses. A novel planar scaled-up passive micromixer is experimentally investigated in this study. The design incorporates a 7-substream uneven interdigital inlet which supplies two liquid species in a parallel arrangement and promotes diffusion along the side walls. Forty-eight staggered teardrop-sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…98.2%, at Re = 0.1). Cook et al (2012) designed a planar scaled-up micromixer consisting of an uneven interdigital inlet, staggered teardrop-shaped obstructions, and wall protrusions. The experimental Investigation at Re = 1˗100 showed that the proposed design achieved the maximum efficiency of 68.5% at Re = 1 because of multi-lamination caused by the uneven interdigital inlet.…”
Section: Obstacles Attached To the Top/bottom Wallsmentioning
confidence: 99%
“…98.2%, at Re = 0.1). Cook et al (2012) designed a planar scaled-up micromixer consisting of an uneven interdigital inlet, staggered teardrop-shaped obstructions, and wall protrusions. The experimental Investigation at Re = 1˗100 showed that the proposed design achieved the maximum efficiency of 68.5% at Re = 1 because of multi-lamination caused by the uneven interdigital inlet.…”
Section: Obstacles Attached To the Top/bottom Wallsmentioning
confidence: 99%
“…Kristina J. Cook et al in her study employed uneven interdigital inlets to investigate her proposed micromixer for the Re ranging between 1 and 100. 32 A series of obstacles in the shape of a teardrop were used to increase the mixing efficiency. Fig.…”
Section: Modeling Assumptions and Fabrication Processmentioning
confidence: 99%
“…Considering the effects due to change in geometry in micro-channel flow, a very effective and simple geometry to increase diffusion is to add a Y splitting section and then recombine the two branches in an inverse Y junction [6][7][8][9]. This configuration is rather simple to be manufactured and can be also used for flow measurements (flow rate) and control.…”
Section: Introductionmentioning
confidence: 99%